Early lactation somatic cell count should be low - Dunham, James R. (Kansas Agricultural Experiment Station, 2012)
Cows and heifers in milk for fewer than 50 days, as shown on the DHIA Somatic Cell Count report, should have a lower average Somatic Cell Count than cows in milk for more than 300 days, if the dry cow mastitis treatment and management programs are effective. The DHIA Somatic Cell Count (SCC) average for a dairy herd is a good evaluation of a mastitis control program. Since leucocytes migrate to the mammary system during periods of subclinical mastitis, the SCC average indicates the amount of subclinical mastitis in a herd. A realistic goal for a herd average SCC is less than 200,000. In many herds with average SCC over 400,000, the average SCC of early lactation cows is higher than that of late lactation cows. This indicates a problem during the dry period, either dry cows are not being cured of mastitis or they are becoming re-infected with mastitis during the dry period.
Keywords: Dairy; Lactation; Somatic cell count; Dry cow